EFFECT OF DIFFERENT pH LEVELS ON THE GROWTH AND SPORULATION OF FUSARIUM OXYSPORUM SCHLECHT. F. SP. LENTIS (VASUDEVA AND SRINIVASAN) THE CAUSAL ORGANISM OF WILT DISEASE OF LENTIL - HIMANSHU BHUSHAN JARUHAR,; AJAY PRASAD, (The Bioscan, 2011)
Effect of pH on the growth and sporulation of Fusarium oxysporum Schlecht . f . sp. lentis (Vasudeva and Srinivansan) after incubation of two weeks in vitro culture in sucrose nitrate medium was studied. pH level 6.0 was found optimum for the growth as well as sporulation of the fungus. Sporulation of chlamydospore was however found best in the pH level 4.0. Further increases in the pH level show retarding effect on growth and sporulation. Size of the spores increases with increase in the pH range.